2. SELF CONCEPT, STUDENT ENGAGEMENT DAN SCHOOL WELL-BEING PADA PEMBELAJARAN JARAK JAUH - Syahnur Rahman; Diyana Maliha Fauziyyah; Nurul Shabilla Nindya Utari; Verena Patrin Sihotang (Fakultas Psikologi Universitas Wijaya Putra, 2022)
School is one environment that has an influence on individuals. This study aims to determine the relationship between self-concept, student engagement, and school well-being. The method used in this research is a literature study and descriptive method with a qualitative approach. Researchers collect data and information related to self-concept, student engagement, and school well-being through supporting data sourced from research journals both nationally and internationally which are search results from Google Scholar, Science Direct, and Elsevier. This research study shows that self-concept and student engagement in school can affect school well-being in students during distance learning.